Gambaran Toxic Masculinity dan Kecenderungan Body Dysmorphic Disorder (BDD) pada Remaja Laki-Laki - Hu, Sarah Magia; Rossalia, Nanda (MANASA, 2025)
Masculinity is often associated with social expectations requiring men to be resilient, strong, and determined. However, these expectations can create social pressures leading to toxic masculinity, which increases the risk of mental health issues such as a tendency toward Body Dysmorphic Disorder (BDD). BDD is characterized by an exaggerated perception of minor or non-existent flaws in one’s appearance. This study aims to explore toxic masculinity and the tendency toward BDD in male adolescents. The research employs a qualitative descriptive approach using structured interviews conducted on high school boys aged 17–18. Three participants were selected based on CMNI-46 screening scores above 119 to ensure they represent the targeted masculinity characteristics. Data were analyzed using thematic analysis, maintaining integrity through triangulation. The findings reveal toxic masculinity and BDD tendencies in male adolescents, shaped by traditional masculinity expectations emphasizing dominance, emotional suppression, and avoidance of vulnerability. Pressure to meet standards, such as achieving an ideal physical image, triggers compulsive behaviors, anxiety, and social isolation, negatively impacting mental health. Factors such as family, culture, social media, religion, economy, and birth order influence masculinity perceptions. The study underscores the need for education and further research to create safe spaces for boys to express emotions without stigma and provide adequate psychological support.